Geographical Condition of Water Availability at Situ Aksan: Documentary Film Study Project - Thomas Dida Avrihansyah; Irwan Sarbeni (Cinematology: Journal Anthology of Film and Television Studies, 2021)
The role of water in Bandung in recent years has become a crisis. One of them is the groundwater crisis in the Situ Aksan area, Bandung. The purpose of this study is to see the relationship between geographical locations in Situ Aksan as the main data for the documentary film project. With the qualitative descriptive method of interviews, observation and study documentation, this research produces sufficient data as an important part of the pre-production of documentary films. This study found that there is a relationship between location and air information problems in people in the area. In addition, the results of this study have been able to become important data in the pre-production, production and post-production of documentary projects. Keywords — Situ Aksan; Towards Water; Geographical Location, Documentary Films